2021
DOI: 10.1371/journal.pone.0246432
|View full text |Cite
|
Sign up to set email alerts
|

A casino in my pocket: Gratifications associated with obsessive and harmonious passion for mobile gambling

Abstract: Mobile gambling differs from land-based and traditional forms of gambling in that the opportunity to place bets and engage with casinos is constantly present and easily accessible. Instead of going to a physical bookmaker or casino, mobile gambling is done quickly and swiftly, anytime, anywhere, with a few taps on a mobile device. Previous studies reveal mobile gambling has managed to reach new audiences especially amongst younger people. Gambling harms can have severe adverse effects on individuals, families … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Contrary to obsessive passion, harmonious passion refers to an independent internalization that causes people to choose and participate in the activity they want ( Luu, 2021 ; Whelan et al, 2021 ). An independent internalization occurs because without any contingencies added to it when individuals realized the importance of activity essential to them.…”
Section: Literature and Hypotheses Developmentmentioning
confidence: 99%
“…Contrary to obsessive passion, harmonious passion refers to an independent internalization that causes people to choose and participate in the activity they want ( Luu, 2021 ; Whelan et al, 2021 ). An independent internalization occurs because without any contingencies added to it when individuals realized the importance of activity essential to them.…”
Section: Literature and Hypotheses Developmentmentioning
confidence: 99%
“…healthcare systems, and developing societal-level messaging that destigmatises GRH. Additionally, digitalisation affects gambling activities in a way that does not apply to alcohol, tobacco or HFSS consumption [1,3]. Therefore, we do not wish to suggest that the PH approaches evident in the scoping review represent an exhaustive list, nor that all approaches in other sectors are necessarily effective for, or relevant to, gambling.…”
Section: Plos Onementioning
confidence: 99%
“…As of 2021, the global online gambling industry alone was worth US $61.5 billion, forecast to rise to US$114.4 billion by 2028 [2]. The increasing accessibility of gambling-such as the products available through smartphones [3]-increases the possibility of gambling-related harms (GRH) [4]. These harms are wide-ranging, covering numerous dimensions (such as financial, emotional or cultural) and they are not restricted to the gambler, also affecting their families and social networks [5].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the dualistic model of passion, previous studies have reported that harmonious passion is closely related to positive work outcomes (e.g., job satisfaction and organizational commitment [ 1 , 2 ]); conversely, obsessive passion is not related to positive work outcomes (e.g., work satisfaction [ 30 ] and work performance [ 2 ]) but to negative ones (e.g., exhaustion and cynicism [ 13 ] and burnout [ 8 ]). Specifically, because employees with harmonious work passion present flexible forms of involvement in their work-related activity, they are more likely to experience positive affect and high levels of task engagement [ 31 ], flow [ 3 ], vitality [ 11 ], and objective performance at work [ 10 ]. However, employees with obsessive work passion display rigid persistence toward work-related activities, which further promotes internal compulsion to engage in work regardless of the personal costs and risks, leading to failed work commitments and task completion as well as damaged interpersonal relationships in the organization [ 3 , 30 ].…”
Section: Theory and Hypothesesmentioning
confidence: 99%